Obesity, Underweight, and Smoking Are Associated with Worse Cardiorespiratory Fitness in Finnish Healthy Young Men: A Population-Based Study - Nikolakaros, Georgios; Vahlberg, Tero; Auranen, Kari; Sillanmäki, Lauri; Venetoklis, Takis; Sourander, Andre (Frontiers in Public Health, 2017)
Background: Obesity and smoking are strongly associated with worse cardiorespiratory fitness (CRF). Most previous studies that have examined the association of body composition with CRF have neither assessed non-linearity nor separately examined the effects of underweight. Thus, very little is known on how underweight affects CRF. Possible joint effects of obesity and smoking on CRF have not been adequately explored. Aims: We examined the association between body mass index (BMI) and smoking with cardiorespiratory fitness (CRF) in 1629 Finnish army conscripts. We focused on non-linear effects of BMI in order to assess the importance of underweight. We also examined whether the co-occurrence of obesity and smoking potentiates their deleterious effects on CRF. Methods: We used the Cooper’s 12-minute run test (12MR) to measure CRF. The 12MR score was analyzed as continuous (linear, polynomial, and restricted cubic spline regression) and categorical. In categorical analyses we used binary logistic regression with the 12MR score in two groups ((low = lowest quintile vs. intermediate/high = quintiles 2 - 5) and multinomial logistic regression with the 12MR score in three groups (low = lowest quintile, intermediate = quintiles 2 and 3, and high = quintiles 4 and 5). Results: Non-linearity in the spline model was statistically significant (p<0.001). In addition, the non-linear models had a clearly better fit than the linear one in terms of Akaike Information Criterion and R-squared values. There was a statistically significant interaction between smoking and BMI (p<0.01). In the categorical analysis, overweight/obese regular smokers were at a particularly high risk of not achieving high CRF. Conclusions: In healthy young men not only overweight/obesity but also underweight may be associated with worse CRF. This provides a potential mechanism for the previously reported association between underweight and increased mortality. The co-occurrence of overweight/obesity and regular smoking may have a deleterious effect on CRF.